1997
DOI: 10.1104/pp.113.3.729
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamate-4-Hydroxylase Expression in Arabidopsis (Regulation in Response to Development and the Environment)

Abstract: Cinnamate-4-hydroxylase (C4H) is the first Cyt P450-dependent monooxygenase of the phenylpropanoid pathway. To study the expression of this gene in Arabidopsis thaliana, a C 4 H cDNA clone from the Arabidopsis expressed sequence tag database was identified and used to isolate its corresponding genomic clone. The entire C4H coding sequence plus 2.9 kb of its promoter were isolated on a 5.4-kb Hindlll fragment of this cosmid. lnspection of the promoter sequence revealed the presence of a number of putative regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(145 citation statements)
references
References 64 publications
6
139
0
Order By: Relevance
“…At least in a qualitative manner, the MetArray expression patterns matched most previously reported data by Northern, RT-PCR, or promoterreporter analyses of single CYP genes (Bell-Lelong et al, 1997;Mizutani et al, 1998), of genes encoding UGTs and glutathione-dependent enzymes (Warnecke et al, 1997;Jackson et al, 2001;Jones et al, 2003;Loutre et al, 2003;Rodriguez Milla et al, 2003), or groups of ABC transporter genes van den Bruˆle and Smart, 2002). A compilation of examples are provided as supplementary information (Supplementary Table 2).…”
Section: Organ Distribution Of Transcriptssupporting
confidence: 65%
“…At least in a qualitative manner, the MetArray expression patterns matched most previously reported data by Northern, RT-PCR, or promoterreporter analyses of single CYP genes (Bell-Lelong et al, 1997;Mizutani et al, 1998), of genes encoding UGTs and glutathione-dependent enzymes (Warnecke et al, 1997;Jackson et al, 2001;Jones et al, 2003;Loutre et al, 2003;Rodriguez Milla et al, 2003), or groups of ABC transporter genes van den Bruˆle and Smart, 2002). A compilation of examples are provided as supplementary information (Supplementary Table 2).…”
Section: Organ Distribution Of Transcriptssupporting
confidence: 65%
“…The single C4H gene from Arabidopsis was cloned and characterized over a decade ago (Table 1; Bell-Lelong et al, 1997;Mizutani et al, 1997); however, the identification of viable C4H mutants was only reported recently. By using the UV-screening method described previously, Schilmiller and coworkers were able to isolate three allelic mutants harboring missense mutations in the Arabidopsis C4H gene.…”
Section: The Shikimate Pathwaymentioning
confidence: 99%
“…For plant transformation, the promoter-terminator cassette from pJR19 (Abbott et al, 2002) was isolated as an EcoRI/HindIII fragment and ligated into pMOG1006 cut with the same enzymes to make pMOG1006-35S. The 35S promoter was later replaced with the Arabidopsis C4H promoter (Bell-Lelong et al, 1997) to make pMOG-C4H. GUS2A-F5H was isolated as a SalI fragment and inserted into SalI-digested pMOG1006-35S or pMOG-C4H plasmids.…”
Section: Pgus2a-f5hmentioning
confidence: 99%